A one-step approach to make cellulose-based hydrogels of various transparency and swelling degrees. (15th April 2018) - Geng, Hongjuan
Highlights: A simple "one-step" method was adopted to make cellulose-based hydrogels. The preparation process can be carried out at room temperature. Addition of MBA obviously shortened the gel formation time. MBA increased the transparency and strength of the hydrogels significantly. Hydrogels with adjustable structure and properties can be obtained. Abstract: This work reports a "one-step" approach to make cellulose-based hydrogels in NaOH/urea aqueous solution via mixing N, N ′-methylene bisacrylamide (MBA) with cellulose solution at room temperature. The hydrogels were revealed to be formed by an addition reaction between the double bonds of MBA and the hydroxyl groups of cellulose. Two states of hydrogels, i.e. the freshly prepared hydrogels and the hydrogels at swelling equilibrium state in deionized water, were prepared. Water retention of the hydrogels can reach up to 330 g H2 O/g dry hydrogel. The freshly prepared hydrogels showed increased mechanical strength and high transparency (94%) with the addition of MBA. The hydrogels at swelling equilibrium state displayed macroporous structures with the pore diameter up to 0.65 mm and showed significantly varied properties with various amount of MBA. The obtained hydrogel could be used as a good blank template for the functionalization of cellulose-based hydrogel.